Saving reed lands by giving economic value to reed - F.W. Croon (Mires and Peat, 2014)
Discussions about the need for renewable energy, the need for nature conservation, the need to double the world’s food production to eliminate hunger, the need to reduce carbon dioxide emission, and the wish to reduce dependency on dwindling oil resources, show that these issues are intimately related and sometimes mutually exclusive. The use of food crops for the production of renewable fuels has resulted in the energy vs. food debate; the use of scarce land and fresh water for the dedicated production of biomass conflicts with food production and nature conservation; the collection of harvest residues and forest wastes as biomass to produce renewable fuels is complex and leaves a CO2 footprint. The several species of reed that grow naturally in deltas, river plains etc. can provide large amounts of biomass but are hardly mentioned in the debates. Harvesting reed does not threaten the nature and the natural functions of reed lands, which are carbon neutral or carbon dioxide sinks. Reed production does not need extensive infrastructure or complex cultivation and does not compete with food production for land and fresh water. Reed lands in many places are under threat of reclamation for economic activities and urbanisation. This trend can be countered if reed is seen to have a proven economic value. In this article I argue that giving a sustainable economic value to reed lands can only be realised if the exploitation is recognised as being environmentally acceptable, commercially feasible and a source of economic gains for all stakeholders. Commercial feasibility can be achieved under present economic conditions only if a reliable supply of considerable volumes of reed at a limited price can be guaranteed.